2011
DOI: 10.3758/s13421-011-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Production benefits both recollection and familiarity

Abstract: Avis par courriel de la disponibilité des revues de la SCP en ligne!Vous voulez savoir quand sera accessible en ligne le prochain numéro de votre revue de la Sociétè canadienne de psychologie préférée? Il est désormais possible de le faire. Inscrivez-vous a `http://notify.apa.org/ et vous serez avisé par courriel de la date de parution en ligne des numéros qui vous intéressent! 98 BODNER, JAMIESON, CORMACK, MCDONALD, AND BERNSTEIN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 55 publications
16
65
0
Order By: Relevance
“…However, we should note that some studies have adopted both R/K and ROC curves using the dual-process signal detection (Yonelinas and Levy 2002) procedures and obtained similar findings on various issues (e.g., Koen and Yonelinas 2010;Ozubko et al 2012). Particularly, there are many studies using R/K and ROC paradigms have found that the proportion of recollection greatly decreases over time (for review, see Sadeh et al 2014).…”
Section: Distinction Between Item and Associative Memoriesmentioning
confidence: 79%
“…However, we should note that some studies have adopted both R/K and ROC curves using the dual-process signal detection (Yonelinas and Levy 2002) procedures and obtained similar findings on various issues (e.g., Koen and Yonelinas 2010;Ozubko et al 2012). Particularly, there are many studies using R/K and ROC paradigms have found that the proportion of recollection greatly decreases over time (for review, see Sadeh et al 2014).…”
Section: Distinction Between Item and Associative Memoriesmentioning
confidence: 79%
“…Along these lines, Ozubko et al (2012) showed that the advantage of reading aloud over reading silently occurred for words for which participants had a recollective experience or for words that were simply deemed to be familiar (regarding recollection, see also Gregg & Gardiner, 1991). The finding of a reliable production effect in recall (Conway & Gathercole, 1987, Exp.…”
Section: Discussionmentioning
confidence: 99%
“…3;Lin & MacLeod, in press) also fits with this observation. As well, Ozubko et al (2012) and Conway and Gathercole (1987) found that participants were more likely to make correct than to make incorrect modality judgments for words that they read aloud than for words that they read silently. Just as individuals can draw upon retrieval of "I said that aloud" to help recognize a previously studied word, so, too, can they make use of retrieving "I mouthed that," "I wrote that," and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply put, the production effect is the better memory observed for items read aloud than for items read silently. In a series of experiments, MacLeod et al showed this to be a large and robust benefit (see also Hourihan & MacLeod, 2008;Ozubko, Gopie, & MacLeod, 2011;. They argued that the mechanism underlying the effect is distinctiveness, with items produced during study having the distinctive additional element in their encoding of having been spoken aloud.…”
mentioning
confidence: 99%